Selective Auditor Quality Effects on Audit Report Lag: Evidence from Financial Risk and R&D Complexity - Bagas Aditya Putra; Bestari Dwi Handayani (Owner : Riset dan Jurnal Akuntansi, 2026)
Prior studies document mixed and inconclusive evidence regarding the determinants of audit report lag (ARL), particularly concerning the role of firm risk and auditor quality in shaping audit timeliness. This study responds to this inconsistency by examining whether auditor quality uniformly enhances audit timeliness or operates conditionally depending on the nature of audit risk. Drawing on agency theory and signaling theory, this study investigates the effects of leverage and research and development (R&D) intensity on ARL, while explicitly testing the contingent role of auditor quality. Using panel data from 17 manufacturing firms listed on the Indonesia Stock Exchange during the 2022–2024 period (51 firm-year observations), this study employs random-effects panel regression with heteroskedasticity-robust standard errors. The results indicate that both leverage and R&D intensity significantly increase audit report lag, reflecting heightened structural financial risk and judgment-intensive audit complexity. However, the moderating analysis reveals a key asymmetry: auditor quality significantly attenuates the positive effect of R&D intensity on ARL, but fails to moderate the relationship between leverage and ARL. These findings demonstrate that the effectiveness of high-quality auditors is selective rather than universal. This study contributes to the audit literature by reconceptualizing auditor quality not merely as a direct determinant of audit timeliness, but as a contingent governance mechanism whose effectiveness depends on the nature of audit risk being more pronounced in mitigating judgment-based complexities arising from innovation activities than structural financial risks.